THE ANALYSIS OF EARNING MANAGEMENT AND FINANCIAL PERFOMANCE BEFORE AND AFTER THE ACQUITION OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Weni Patanduk; Abdul Rahman Laba; Mursalim Nohong (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
One strategy that companies can do to achieve a strong market is by improving company performance, strengthening capital conditions and expanding. This study aims to determine earnings management practices with a pattern of increasing profits before making acquisitions and differences in financial performance before and after companies make acquisitions. Samples are companies listed on the Indonesia Stock Exchange in 2016 to 2018 with a purposive sampling approach. Data were analyzed using IBM SPPS Statistics 23. The results of this study indicate that: (1) There is no earnings management practice by the acquirer by increasing the accrual value before and acquisition, (2) Financial performance proxied by CR, TATO, NPM, and DER, did not experience significant differences, both before and after the acquisition. (3) Financial performance, which is proxied by CR, NPM, TATO, DER, which is tested by Independent Paired Sample Test, shows that there is no significant difference before and after acquisition. (4) Financial performance, which is proxied by CR, NPM, TATO, DER, which is tested by the Wilcoxon Sign Rank Test shows that CR, DER and TATO, there are no significant differences before and after the acquisition. The Net Profit Margin experienced significant financial performance differences and experienced an increase before and after the acquisition.